A guerrilla guide to refusal - Culp, Andrew, 1984- (University of Minnesota Press, 2022)
"This book is an unexpected approach to philosophy from a guerrilla-logic point of view. Harnessing critical theory to reimagine counterinsurgency, guerrilla warfare, and interventions beyond the political mainstream, it takes us on a journey through anarchist infowars, queer outlaws, and black insurgency, providing powerful new insight into contemporary political movements that pose no demands, refuse labels, and offer no solutions"--